Case Report: Irreversible Watery Diarrhea, Severe Metabolic Acidosis, Hypokalemia and Achloridria Syndrome Related to Vasoactive Intestinal Peptide Secreting Malignant Pheochromocytoma - Negro, Aurelio; Verzicco, Ignazio; Tedeschi, Stefano; Campanini, Nicoletta; Zanelli, Magda; Negri, Emanuele; Farnetti, Enrico; Nicoli, Davide; Palladini, Barbara; Santi, Rosaria; Cunzi, Davide; Calvi, Anna; et al. (Frontiers in Endocrinology, 2021)
Background: Pheochromocytoma (PHEO) clinical manifestations generally mirror excessive catecholamines secretion; rarely the clinical picture may reflect secretion of other hormones. Watery diarrhea, hypokalemia and achlorhydria (WDHA) is a rare syndrome related to excessive secretion of vasoactive intestinal peptide (VIP). Clinical case: A 73-year-old hypotensive man affected by adrenal PHEO presented with weight loss and watery diarrhea associated with hypokalemia, hyperchloremic metabolic acidosis (anion gap 15 mmol/l) and a negative urinary anion gap. Abdominal computed tomography scan showed a right adrenal PHEO, 8.1 cm in maximum diameter, with tracer uptake on 68GaDOTA-octreotate positron emission tomography. Metastasis in lumbar region and lung were present. Both chromogranin A and VIP levels were high (more than10 times the normal value) with slightly elevated urine normetanephrine and metanephrine excretion. Right adrenalectomy was performed and a somatostatin analogue therapy with lanreotide started. Immunostaining showed chromogranin A and VIP co-expression, with weak somatostatin-receptor-2A positivity. In two months, patient clinical conditions deteriorated with severe WDHA and multiple liver and lung metastasis. Metabolic acidosis and hypokalemia worsened, leading to hemodynamic shock and exitus. Conclusions: A rare case of WDHA syndrome caused by malignant VIP-secreting PHEO was diagnosed. High levels of circulating VIP were responsible of the rapidly evolving clinical picture with massive dehydration and weight loss along with severe hyperchloremic metabolic acidosis and hypokalemia due to the profuse untreatable diarrhea. The rescue treatment with lanreotide was unsuccessful because of the paucity of somatostatin-receptor-2A on VIP-secreting PHEO chromaffin cells.